2006
DOI: 10.1111/j.1460-9568.2006.04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐ and glucocorticoid‐inducible kinase (SGK) is a target of the MAPK/ERK signaling pathway that mediates memory formation in rats

Abstract: We have previously demonstrated that serum- and glucocorticoid-inducible kinase (SGK) plays a causal role in facilitating memory formation of spatial learning in rats, but the SGK signaling pathway involved in spatial memory formation is not known. The mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) also plays an important role in memory formation. We therefore examined whether SGK is a downstream target of the MAPK/ERK signaling cascade and whether ERK signaling to SGK mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
3
25
1
Order By: Relevance
“…22,23 Mechanical stretch stimulated strong phosphorylation of extracellular signal-regulated kinase (ERK)1/2 and p38, and moderate phosphorylation of c-Jun N-terminal kinase (JNK) ( Figure 2A). We then inhibited different MAPKs in venous SMC and found that inhibition of MEK1 with inhibitor (U0126) or MEK1 dominant negative, but not inhibitor of p38 or JNK, significantly inhibited stretch-induced increases in SGK-1 protein level (Figure 2B and 2C).…”
Section: Mek1 Signaling Pathway Mediates Mechanical Stretch-induced Smentioning
confidence: 99%
“…22,23 Mechanical stretch stimulated strong phosphorylation of extracellular signal-regulated kinase (ERK)1/2 and p38, and moderate phosphorylation of c-Jun N-terminal kinase (JNK) ( Figure 2A). We then inhibited different MAPKs in venous SMC and found that inhibition of MEK1 with inhibitor (U0126) or MEK1 dominant negative, but not inhibitor of p38 or JNK, significantly inhibited stretch-induced increases in SGK-1 protein level (Figure 2B and 2C).…”
Section: Mek1 Signaling Pathway Mediates Mechanical Stretch-induced Smentioning
confidence: 99%
“…Serum-and glucocorticoidinducible kinase (SGK) is another downstream target of PI-3K-PDK1 (phosphoinositide-dependent protein kinase-1) signaling (Kobayashi and Cohen, 1999). SGK1 has recently been demonstrated to play an important role in spatial memory formation (Tsai et al, 2002;Lee et al, 2006). A higher SGK mRNA level was found in fast-learning rats than slow-learning rats in the water maze learning task.…”
Section: Introductionmentioning
confidence: 96%
“…Plasmid DNA was constructed as described previously (Chao et al, 2006;Lee et al, 2006). The sgk gene has different isoforms, and here we examined sgk1.…”
Section: Methodsmentioning
confidence: 99%
“…PDK1 phosphorylates SGK1 at threonine-256, which is required in hippocampal area CA1 for spatial memory formation (Lee et al 2006). Further, SGK1 is phosphorylated at serine-78 by ERK (Lee et al 2006). This phosphorylation is not important for spatial memory formation but it is required for contextual fear LTM formation ).…”
Section: Pi3kmentioning
confidence: 99%